Neurotuberculosis: Different facets of a single disease - Paudel, Raju`; Subedi, Ram Chandra; Bhatta, Manali; Adhikari, Rupendra Bahadur; Sedain, Gopal; Bastola, Shova; Parajuli, Ranjana; Yadav, Jitendra; Pandey, Suvekchya; Paudel, Pratik; Paudel, Sharma; Dawadi, Kapil; et al. (Grande Medical Journal, 2025)
Tuberculosis (TB) can affect the meninges, brain or spinal cord, individually or in various combinations leading to neurotuberculosis. Tuberculous meningitis (TBM) is the most severe manifestation of central nervous system tuberculosis, with extremely high mortality (20-50%) and severe neurological morbidity among survivors. In spite of spectacular progress in diagnostic techniques and therapeutic approaches, TBM represents a serious global health burden, especially in tuberculosis-endemic areas and in immunocompromised groups. This review combines the existing evidence on TBM epidemiology, pathophysiology, clinical presentation, diagnostic strategies, and evidence-based management strategies. We have included developments in molecular diagnostics such as GeneXpert Ultra, new drug regimens including bedaquiline and linezolid, and adjuvant therapies such as corticosteroids and thalidomide. Drug-resistant TBM, pediatric age groups, and HIV coinfection situations are also emphasized with particular focus. The review includes case based illustrations and imaging to cover various categories of tubercular meningitis and spinal tuberculosis with its complications so that pragmatic approach can be utilized in the diagnosis and management of various aspects of neurotuberculosis.